Smart City Development Analysis: A Comparison Of Kampala And Jakarta City - Gloria Nambassa; Suswanta Suswanta (Journal of Government and Politics (JGOP), 2025)
At present, rapid technological advancements influence various facets of life, shaping economic, social, and infrastructural landscapes. However, these advancements also raise concerns about uncontrolled population growth and the challenges associated with urbanization. As global populations expand, cities face the urgent task of accommodating increasing numbers while ensuring sustainable development. The complexity of these issues necessitates proactive interventions to maintain a balance between technological progress and environmental sustainability.